PD‐1 blockade: a therapeutic option for treatment of metastatic Merkel cell carcinoma. (23rd October 2016) - Winkler, J.K.; Bender, C.; Kratochwil, C.; Enk, A.; Hassel, J.C.
Summary: The immune system is extremely important in the development and progression of Merkel cell carcinoma (MCC). Immune checkpoint blockade has recently been shown to enable efficacious treatment of a variety of tumours. We report the use of an anti‐programmed death receptor 1 (PD‐1) antibody for treatment of a patient with metastatic MCC. An 80‐year‐old patient with metastatic MCC received off‐label treatment with the anti‐PD‐1 antibody pembrolizumab after the disease had progressed during therapy with oral etoposide. A positron emission tomography (PET) computed tomography scan performed after three cycles of pembrolizumab revealed responses to therapy with reduced size of the adrenal gland metastases and less PET activity in the adrenal gland and lymph node metastases. Treatment was resumed owing to disease progression after a treatment‐free interval of > 4 months. During subsequent months of treatment, the size of the metastases stabilized and uptake of nuclide by all tumour sites once again decreased. These results reveal the potential efficacy of an anti‐PD‐1 antibody for treatment of metastatic MCC. Thus, they contribute to currently limited data on the use of anti‐PD‐1 antibodies for the treatment of MCC. Moreover, this is the first report of successful resumption of treatment of metastatic MCC with an anti‐PD‐1 antibody. Results from ongoing trials will contribute to determination of the relevance of PD‐1 blockade in metastatic MCC. Abstract : What's already known about this topic? Immune escape mechanisms are involved in the progression of Merkel cell carcinoma (MCC). Preliminary results have been obtained from a phase II trial evaluating pembrolizumab for the treatment of MCC. Complete response to pembrolizumab has been observed for a patient with MCC (phase I trial). What does this study add? Positron emission computed tomography evaluation revealed a significant response to treatment with pembrolizumab. Resumption of pembrolizumab after disease progression was successful. Programmed death ligand 1 expression and immune infiltration were assessed histologically. Linked Comment: Cassler and Brownell. Br J Dermatol 2017; 176 :18 .